Progression markers of coronary calcification. (14th October 2021) - Sedykh, D Y U; Barbarash, O L; Kashtalap, V V; Hhryachkova, O N; Kokov, A N; Shibanova, I A
Abstract: Aim: To evaluate the relationship between clinical parameters, biomarkers of bone turnover and the progression of coronary artery calcification (CAC) in patients with stable coronary heart disease (CHD) based on long-term (5 years) follow-up. Material and methods: The single-center, prospective, non-randomized observational study included 111 men with CHD, admitted for CABG. All patients in the preoperative period underwent the following procedures: color duplex scanning (CDS) of the brachiocephalic arteries (BCA), multi-slice computed tomography (MSCT) coronary angiography to assess the degree of CAC using the Agatson score (calculation of the coronary artery calcium score – CACS), estimation of femoral neck bone mineral density with the T-score calculation and clinical assessment of biomarkers of bone metabolism (calcium, phosphorus, calcitonin, osteopontin, osteocalcin, osteoprotegerin (OPG), alkaline phosphatase, parathyroid hormone). The vital status of patients was ascertained after 3–5 years of follow-up after CABG, CDS of the BCA and MSCT-coronary angiography were repeated. To identify the most significant clinical and anamnestic risk factors and form a model of predictors of CAC progression, patients were divided into two groups depending on the high increase in CACS (an increase in the score of more than 100 Agatston units (AU). Results: 16 (14.4%) out of 111 patients failed to establish contact for the next stage of the study. In 4 (3.6%) cases death was registered (3 – fatal myocardial infarction, 1 – fatal stroke). The CAC progression was assessed in 91 patients (81.9%). Patients who showed signs of CAC progression comprised a group of 60 (65.9%) patients; without CAC progression – 31 (34.1%) patients. The "end points" in the groups were comparable and were detected in 18 cases (19.7%): recurrent angina in 16 patients (p=0.368), non-fatal myocardial infarction in 1 (p=0.162) and 1 emergency stenting (p=0, 162) of the coronary artery that was not subjected to CABG. The risk model for CAC progression included an initial decrease in femoral neck bone mineral density and nonadherence to statins for 5 years after CABG (p=0.001). Conclusion: 65.9% of men with stable CHD showed the signs of CAC progression for 5 years after CABG, according to MSCT. The main predictors of CAC were: low cathepsin K levels and low bone mineral density in the preoperative period, low OPG 5 years post-CABG. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Federal State Budgetary Institution "Research Institute for Complex Issues of Cardiovascular Diseases"; 6, Sosnovy Blvd, Kemerovo, 650002, Russia